2020
DOI: 10.3390/pr8101303
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Inner Surface State of Thick-Walled Tubes by Heat Treatments with Internal Quenching Considering a Simulation Based Optimization

Abstract: Internal Quenching is an innovative heat treatment method for difficult to access component sections. Especially, the microstructure, as well as the residual stress state at inner surfaces, of thick-walled tubes can be adjusted with the presented flexible heat treatment process. Based on multiphysical FE-models of two different steels, a simulative optimization study, considering different internal quenching strategies, was performed in order to find the optimal cooling conditions. The focus hereby was on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…7 In another study, Kamal et al employed the Sachs technique to specify the residual stresses in SS304 thick-walled autofrettaged cylinders and indicated that the compressive residual stresses cause an increase in the hardness of internal tube surface and the tensile residual stresses cause a decrease in the hardness of external tube surface. 8 Recently, Mu¨hl et al 9 used the Sachs technique to determine the residual stresses of thick-walled tubes. The Sachs method can also be utilized to specify the axisymmetric residual stresses in the SPD techniques.…”
Section: Introductionmentioning
confidence: 99%
“…7 In another study, Kamal et al employed the Sachs technique to specify the residual stresses in SS304 thick-walled autofrettaged cylinders and indicated that the compressive residual stresses cause an increase in the hardness of internal tube surface and the tensile residual stresses cause a decrease in the hardness of external tube surface. 8 Recently, Mu¨hl et al 9 used the Sachs technique to determine the residual stresses of thick-walled tubes. The Sachs method can also be utilized to specify the axisymmetric residual stresses in the SPD techniques.…”
Section: Introductionmentioning
confidence: 99%